Pengaruh Media SoftBook Shapes Terhadap Kemampuan Anak Mengenal Bentuk Geometri Anak Usia 4-5 Tahun di TK GKPI Tarutung Kota - Wina Cindy Miranti Lumbantobing; Uranus Zamili; Emmi Silvia Herlina (Institut Nalanda, 2024)
The purpose of this study was to determine the effect of the use of SoftBook Shapes Media on Children's Ability to Recognize Geometric Shapes of Children Aged 4-5 Years in GKPI Kindergarten Tarutung City. The research hypothesis is: